Tales of three worlds : archaeology and beyond : Asia, Italy, Africa : a tribute to Sandro Salvatori - Salvatori, Sandro,; Usai, Donatella,; Tuzzato, Stefano,; Vidale, Massimo, (Archaeopress Archaeology, 2020)
Tales of Three Worlds collects, as a sign of gratitude and affection, a series of papers by many authors who, in different times, contexts and contingencies, had the luck to meet Sandro Salvatori, and share with him a path of knowledge and mutual personal acquaintance. The book is divided in three sections: his long years of work in Middle Asia, from the plains of Sistan to those of the Indus, the coasts of the Omani peninsula and southern Turkmenistan; Sandro's activities in Italy, as an officer of the Archaeological Superintendency (Ministry of Cultural Heritage) of his region; and the prehistory of north-eastern Africa, a context in which Sandro could work in full scientific and familiar ease, as he was prevented from doing in other situations.